Revista centenario : (La Nación, 2005)
Los visionarios del siglo -- Alberto Galindo -- Angelino Vargas Perdomo -- Maximiliano Duque Gómez -- Humberto Tafur Charry -- Jenaro Víctor Díaz Jordán -- Reinaldo Matiz Trujillo -- Leonidas Lara -- Luis Ignacio Andrade Díaz -- Joaquín García Borrero -- Rafael Azuero Manchola -- Guillermo Plazas Alcid -- Héctor Polanía Sánchez -- Felio Andrade Manrique -- Los gobernadores del siglo -- Nidia Quintero de Balcázar -- Misael Pastrana Borrero -- Rodrigo Lara Bonilla -- Rodrigo Villalba Mosquera -- Monseñor Esteban Rojas Tovar -- Monseño Ismael Perdomo Borrero -- Monseñor Luis Calixto Leyva Charry -- Julián Motta Salas -- Reinaldo Polanía Polanía -- Tulia Rosa Espinosa Celis -- Jorge Villamil Cordovéz -- José Antonio Cuéllar "Rumichaca" -- José Eustasio Rivera -- Ricardo Borrero Álvarez -- Inés García de Durán